A conscious rat model involving bradycardia and hypotension after oral administration: a toxicokinetical study of aconitine. (3rd June 2017) - Zhang, Panpan; Kong, Dezhi; Du, Qian; Zhao, Jing; Li, Qing; Zhang, Jianghua; Li, Tonghui; Ren, Leiming
Abstract: 1. A model of aconitine-induced bradycardia and hypotension, which is similar to aconitine poisoning in humans, was constructed in conscious rats by oral administration. 2. Blood pressure (BP) and heart rate (HR) of Sprague-Dawley rats were measured using a volume pressure recording (VPR) system. The pharmacokinetics of toxic doses of aconitine and its metabolites were analyzed using UPLC-MS/MS. 3. The HR was significantly decreased by 29% at 2 h after oral administration of 200 μg/kg aconitine. When the dose was increased to 400 μg/kg, systolic BP and diastolic BP were significantly decreased by 11% and 12% at 2 h after the administration, except when bradycardia occurred at 2 h and 4 h. The drug concentration-time curve showed a double-peak phenomenon in rats administered a 400 μg/kg dose. The AUC0–12 h value in the 400 μg/kg group significantly increased 0.8-fold compared to the 200 μg/kg group. Moreover, a high plasma concentration of 16- O -demethyaconitine was found in the rats that received two toxic doses. 4. In conclusion, bradycardia and hypotension are induced in conscious rats by a toxic dose of aconitine (400 μg/kg), and there was no significant difference in dose-normalized AUC0–12 h values between oral administrations of 200 μg/kg and that of 400 μg/kg. However, the dose-normalized C max and AUC0–12 h values in 200 μg/kg and 400 μg/kg groups were significantly smaller than those in 100 μg/kg group. The metabolites of aconitine, 16- O -demethyaconitine, and benzoylaconitine may also contribute to the hypotensive response.